2016
DOI: 10.1007/s13577-016-0132-z
|View full text |Cite
|
Sign up to set email alerts
|

Induction and differentiation of adipose-derived stem cells from human buccal fat pads into salivary gland cells

Abstract: Atrophy or hypofunction of the salivary gland because of aging or disease leads to hyposalivation that affects patient quality of life by causing dry mouth, deterioration of mastication/deglutition, and poor oral hygiene status. Current therapy for atrophy or hypofunction of the salivary gland in clinical practice focuses on symptom relief using drugs and artificial saliva; therefore, there is still a need to develop new therapies. To investigate potential novel therapeutic targets, we induced the differentiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 31 publications
2
11
0
Order By: Relevance
“…In the present study, significant intergroup differences were observed for body and SG weights. In a previous study, RI exposed SGs showed atrophy of parenchyma, tissue necrosis, and fibrosis resulting from inflammation 17 , and in another, it was suggested simultaneous AdMSCs transplantation might protect SG cells from atrophied and act to regenerate acinar cells and restore saliva volume 22 . In the present study, salivary lag times were shorter and salivary flow rates were significantly higher in the RI + AdMSCs group than in the RI + PBS sham group, which also suggests AdMSCs protect SG cells against RI.…”
Section: Discussionmentioning
confidence: 95%
“…In the present study, significant intergroup differences were observed for body and SG weights. In a previous study, RI exposed SGs showed atrophy of parenchyma, tissue necrosis, and fibrosis resulting from inflammation 17 , and in another, it was suggested simultaneous AdMSCs transplantation might protect SG cells from atrophied and act to regenerate acinar cells and restore saliva volume 22 . In the present study, salivary lag times were shorter and salivary flow rates were significantly higher in the RI + AdMSCs group than in the RI + PBS sham group, which also suggests AdMSCs protect SG cells against RI.…”
Section: Discussionmentioning
confidence: 95%
“…(); g Farre‐Guasch, Marti‐Page, Hernadez‐Alfaro, Klein‐Nulend, and Casals (); h Broccaioli et al. (); i Kawakami, Ishikawa, Tanaka, and Mataga ().…”
Section: Characteristics Of Human Dedifferentiated Fat Cells—in Vitromentioning
confidence: 99%
“…+Means cell is positive for this CD marker; -means cell is negative for this CD marker. The superscript letter next to the + or -sign refers to the study that reported that finding: aKou et al (2014); b Tsurumachi et al (2016); c Kishimoto et al (2014); d Matsumoto et al (2008); e Watson et al (2014); f Poloni et al (2012); g Farre-Guasch, Marti-Page, Hernadez-Alfaro, Klein-Nulend, and Casals (2010); h Broccaioli et al (2013); iKawakami, Ishikawa, Tanaka, and Mataga (2016).…”
mentioning
confidence: 99%
“…Both animal and human experiments have verified that ADSCs could represent a safe treatment strategy for salivary gland damage[ 40 , 114 , 115 , 117 , 120 , 123 ].…”
Section: Salivary Gland Damagementioning
confidence: 99%